Evaluation of performance of some industrial companies In the default reference comparison method Field study in the public companies of cement (Iraqi - North - South - النعيمي صلاح عبد القادر; سعيد سناء عبد الرحيم; محسن سعدون (Journal of Economics and Administrative Sciences, 2009)
The increasing Global Competitive and the continuous improvement in information technology has led the way to the development of the modern systems and using modern techniques. One of these techniques is benchmarking style and Total Quality Management all of them are used to improve the production process and target rid from the losts on the other side. The Benchmarking style has become a very important for all the industrial systems and the serving systems as well. And an instrument to improve their performance specially those which are suffering from the highness of the costs or waste in time on the other side. This study aims to depend on virtual Benchmarking style in the evaluation of the performance of the industrial companies by designing a computer program which leads to the counting of the points and the standards of performance evaluation for the industrial companies to set up a virtual company from a real data and to compare between companies to find out the performance gap inside it and the attempt cancel or cease the gap by pointing out the reasons behind it. The study also aims to convince the organizations and the Iraqi industrial companies to applicate the Benchmarking style inside them and this will take part in the increasing of the performance of these organizations and to be aware of the reality of the process of evaluation in the Iraqi industrial field. The importance of this study comes from the importance of the Virtual Benchmarking, as it is a very good style to improve the organization performance that cannot find the best organization in its field. The study also presents produce a performance standard suitable to the sample of the study towards the achievement of a good performance.